2010
DOI: 10.1016/j.ejcts.2009.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Strain rate imaging would predict sub-clinical acute rejection in heart transplant recipients

Abstract: SR imaging is of potential clinical value for monitoring acute rejection in heart transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
2
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 21 publications
(35 reference statements)
4
41
2
5
Order By: Relevance
“…Our findings are in concordance with most of previously published animal 10,11 and human 12,13 data. The heart graft rejection is characterized by immune cell infiltration, edema and myocyte damage, which results in impaired mechanical LV function, and decrease in strain.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings are in concordance with most of previously published animal 10,11 and human 12,13 data. The heart graft rejection is characterized by immune cell infiltration, edema and myocyte damage, which results in impaired mechanical LV function, and decrease in strain.…”
Section: Discussionsupporting
confidence: 83%
“…Strain has shown to be more sensitive to early LV changes than LV EF in various pathologies 6 , and it has proven superior in prognosis prediction 7,8 . In the field of heart transplantation, the speckle tracking derived strain has been recently applied, normal values for clinically stable heart transplant recipients were established 9 , and an association between impaired strain and acute rejection was demonstrated in both animal 10,11 and human studies [12][13][14] . The aim of our study was to investigate the utility of speckle tracking derived strain analysis in the diagnosis of acute graft rejection in heart transplant recipients with preserved ejection fraction, and in detecting early subclinical phases of acute rejection.…”
Section: Introductionmentioning
confidence: 99%
“…Three smaller studies have also demonstrated that Em significantly reduced in allograft rejection (23,38,39). On the other hand, other studies on 1500 biopsies in nearly 450 patients reported no association between acute allograft rejection and Em (40)(41)(42)(43)(44)(45)(46). Our study found that both tricuspid and mitral annular early (Em), but not late (Am), diastolic velocities were significantly different in the patients with acute allograft rejection.…”
Section: Discussionsupporting
confidence: 45%
“…Stengel et al (45) showed that Am and mitral annular systolic contraction velocity were higher in patients with higher degrees of rejection. Likewise, Kato et al indicated that neither conventional echocardiographic indices nor Em or the E/Em mitral flow ratio could differentiate patients with and without allograft rejection (41).…”
Section: Discussionmentioning
confidence: 99%
“…These characteristics support the advantages of this technology with respect to routine application in the management and surveillance of pediatric heart transplant patients. Strain and strain rate have recently been shown to have a high sensitivity for detecting acute rejection compared with endomyocardial biopsy in adult transplant recipients [12]. Interestingly, transplant recipients had, on the average, a higher fractional shortening than age-and sex-matched control subjects.…”
Section: Discussionmentioning
confidence: 93%